Penerapan Pencegahan Risiko Jatuh Oleh Petugas di Ruang Perawatan Stroke - Desi Aprianti; Mutiara Nitantri; Serly Apriani; Arnila Ousartika; Dwi Mulyantika; Bayu Aji; Sagita Agustina; Vega Pransiska; Oktarina Panggabean; Lilik Pranata; Bangun Dwi Hardika; M. K. Fitriani Fruitasari (Kampurui Jurnal Kesehatan Masyarakat, 2022)
Prevention The risk of falling is very important, especially for patients with stroke disorders, this must be done by caring officers in order to achieve a holistic and comprehensive service. The purpose of the study was to see the application of Fall Risk Prevention by Officers in the Stroke Treatment Room. The research design used a descriptive survey with a questionnaire instrument, with a total of 13 research samples, with the results of the study that 13 (100%) samples had implemented Fall Risk Prevention by Officers in the Stroke Treatment Room. These results indicate that the officers have been able to prevent the risk of falling. Suggestions for continuous monitoring and training for stroke care room officers regarding fall risk screening.